Perlindungan Lahan Pertanian Pangan Berkelanjutan dalam Mendukung Pelestarian Subak - Suryawan, Made Putra (Badan Riset dan Inovasi Daerah Provinsi Bali, 2018)
In the Government Regulation Number 23 Year 1982 concerning irrigation, in Article 1 (h) it is affirmed the meaning of